"Country Boys Spit and Dip": Masculinity and Rural Adolescent Smokeless Tobacco Use. Issue 2 (June 2021) - Helme, Donald W.; Morris, Edward; de la Serna, Ana; Zelaya, Carina; Oser, Carrie; Knudsen, Hannah K.
While tobacco use nationwide is declining, smokeless tobacco (SLT) use remains steady, particularly among men in rural areas. Despite the harms of SLT, researchers know little about what initiates and sustains this use. In this study, we argue that SLT persistence is encouraged by its salience as an emblem of rural manhood. Based on interviews with 64 male and 19 female rural high school students we find that SLT symbolizes rural masculinity, and that many boys "spit and dip" to perform their status as rural men. We specify several peer, family, and community mechanisms that undergird this process. Finally, we discuss implications for men's health research and intervention efforts.